On the relationship between pragmatic knowledge and language proficiency among Iranian male and female undergraduate EFL learners - Atieh Farashaiyan; Tan, Kim Hua (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The purpose of this study was, firstly, to investigate the relationship between pragmatic knowledge and language proficiency, i.e. whether the learners with different proficiency levels perform differently in a pragmatic test. Secondly, the study aimed at exploring the relationship between gender and language proficiency and pragmatic knowledge. That is, the study examined whether there is any significant difference between the performance of males and females regarding their pragmatic knowledge and language proficiency. 120 university students including 60 freshmen and 60 seniors majoring in English Translation from Bandar Abbes Azad University were selected randomly. The participants were placed in the beginning, intermediate and advanced levels based on the results of the proficiency (TOEFL) test. Then, a pragmatic competence test (MDCT) was used to determine the extent of participants’ pragmatic knowledge. The calculated data were analyzed through an inferential statistics. The findings of the study obtained through statistical analyses indicated that a) there was no significant relationship between pragmatic knowledge and language proficiency. In other words, the learners with different proficiency levels did not perform differently in the pragmatic test; b) female participants performed better in pragmatic and proficiency tests.